2018
DOI: 10.1007/s00125-018-4744-6
|View full text |Cite
|
Sign up to set email alerts
|

Basal fatty acid oxidation increases after recurrent low glucose in human primary astrocytes

Abstract: Aims/hypothesisHypoglycaemia is a major barrier to good glucose control in type 1 diabetes. Frequent hypoglycaemic episodes impair awareness of subsequent hypoglycaemic bouts. Neural changes underpinning awareness of hypoglycaemia are poorly defined and molecular mechanisms by which glial cells contribute to hypoglycaemia sensing and glucose counterregulation require further investigation. The aim of the current study was to examine whether, and by what mechanism, human primary astrocyte (HPA) function was alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…ACC is inhibited by phosphorylation via the energy sensor adenosine monophosphate (AMP)-activated protein kinase (AMPK), which links energy deficiency with mitochondrial FAO (Figure 4.3). Recurrent low glucose exposure has been shown to activate AMPK and increase FAO dependency in astrocytes (Weightman Potter et al, 2019). In another study, astrocyte activation with the ciliary neurotrophic factor (CNTF) was also shown to activate AMPK and increases FAO and ketolysis (Escartin et al, 2007).…”
Section: Fa Oxidation (Fao) In Astrocytes: the "Missing Link"mentioning
confidence: 98%
“…ACC is inhibited by phosphorylation via the energy sensor adenosine monophosphate (AMP)-activated protein kinase (AMPK), which links energy deficiency with mitochondrial FAO (Figure 4.3). Recurrent low glucose exposure has been shown to activate AMPK and increase FAO dependency in astrocytes (Weightman Potter et al, 2019). In another study, astrocyte activation with the ciliary neurotrophic factor (CNTF) was also shown to activate AMPK and increases FAO and ketolysis (Escartin et al, 2007).…”
Section: Fa Oxidation (Fao) In Astrocytes: the "Missing Link"mentioning
confidence: 98%
“…While NTS astrocyte integration of glycaemic status appears important for the physiological response to low glucose, what remains to be determined is whether astrocyte glucose sensitivity is reduced after recurrent hypoglycaemia, which may lead to blunted CNS glucose sensitivity and attenuation of the CRR [103] . In vitro, human primary astrocytes show metabolic adaptations following recurrent exposure low glucose levels, which has been suggested reflect a compensatory response to preserve function [104] . As discussed above, under sustained hypoxia astrocytes contribute to long-term adaptive changes in the physiological response to this stimulus, raising the possibility that this may also be true in the context of hypoglycaemia.…”
Section: Regulation Of Physiology By Nts Astrocytesmentioning
confidence: 99%
“…These cells have a higher ability to increase mitochondrial glutamine and long-chain fatty acid usage as substrates for oxidation, but not glucose oxidation. Mitochondria are able to adapt by changing their dependency and flexibility for specific oxidation substrates, to maintain the energy supply [ 43 ]. The transition in fuel choice allows for maintenance of energy and glucose homeostasis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%